High-intensity intermittent exercise increases serum levels of chitinase 3-like protein-1 and matrix metalloproteinase-9 in persons with multiple sclerosis - Bilek, Furkan; Ercan, Zubeyde; Deniz, Gulnihal; Ozgul, Sinem; Demir, Caner Feyzi (Elsevier, 2024)
The study aimed to evaluate the effect of high-intensity intermittent exercise (HIIE) on serum levels of MMP-9 and CHI3L1 in multiple sclerosis. Study group received HIIE twice a week for 12 weeks, while control group received no treatment. In intra-group comparison, study group showed a significant increase in MMP-9 and CHI3L1 levels, while control group showed no significant difference. In intergroup comparison, a significant difference was found only in CHI3L1 levels after treatment. The increase in MMP-9 and CH3L-1 concentrations in study group suggests that these biomarkers may play a role in regulating specific skeletal muscle adaptations due to HIIE.
Keywords: Multiple sclerosis; MMP-9; High-intensity interval exercise; Biomarker